Association of monocyte and lymphocyte ratio with risk of abdominal aortic calcification - Wenting Yan; Tingting Hu (PLoS ONE, 2025)
Objectives The aim of the study was to evaluate the relationship between monocyte and lymphocyte ratio (MLR) with severe AAC. Methods This cross-sectional study enrolled 3041 patients with AAC from the National Health and Nutrition Examination Survey 2013–2014. Abdominal aortic calcification detected with dual-energy X-ray absorptiometry was quantified using the Kauppila score system. We measured white blood cell, neutrophil, lymphocyte counts, monocyte counts, red blood cell, calcium, 25-VitD3, and phosphorus levels in blood samples. Multivariate logistic regression was performed to examine the association between MLR (as a qualitative or quantitative variable) and severe AAC morbidity. Results Severe AAC was detected in 273 (9.0%) participants. Multivariate logistic regression analysis indicated that high MLR was an independent predictor of severe AAC (odds ratio [OR] 2.80, 95% confidence interval [CI] 1.04–7.50; P = 0.041). Conclusions Elevated MLR levels are independently associated with higher odds for severe AAC, which can serve as a new risk factor in clinical practice.